Image-Guided Pediatric Surgery Using Indocyanine Green (ICG) Fluorescence in Laparoscopic and Robotic Surgery - Esposito, Ciro; Settimi, Alessandro; Del Conte, Fulvia; Cerulo, Mariapina; Coppola, Vincenzo; Farina, Alessandra; Crocetto, Felice; Ricciardi, Elisabetta; Esposito, Giovanni; Escolino, Maria (Frontiers in Pediatrics, 2020)
Background: Indocyanine green (ICG)-guided near-infrared fluorescence (NIRF) has been recently adopted in pediatric minimally invasive surgery (MIS). This study aimed to report our experience with ICG-guided NIRF in pediatric laparoscopy and robotics and evaluate its usefulness and technique of application in different pediatric pathologies. Methods: ICG technology was adopted in 76 laparoscopic and/or robotic procedures accomplished in a single division of pediatric surgery over a 24-month period (January 2018-January 2020): 40 (37 laparoscopic, 3 robotic) left varicocelectomies with intra-operative lymphography; 13 (10 laparoscopic, 3 robotic) renal procedures: 7 partial nephrectomies, 3 nephrectomies and 3 renal cyst deroofings; 12 laparoscopic cholecystectomies; 5 robotic tumor excisions; 3 laparoscopic abdominal lymphoma excisions; 3 thoracoscopic procedures: 2 lobectomies and 1 lymph node biopsy for suspected lymphoma. The ICG solution was administered into a peripheral vein in all indications except for varicocele and lymphoma in which it was respectively injected into the testis body or the target organ. Regarding the timing of the administration, the ICG solution was administered intra-operatively in all indications except for cholecystectomy in which the ICG injection was performed 15-18 hours before surgery. Results: No conversions to open or laparoscopy occurred. No adverse and allergic reactions to ICG or other postoperative complications were reported. Conclusions: Based upon our 2-year experience, we believe that ICG-guided NIRF is a very useful tool in pediatric MIS to perform a true imaged-guided surgery, allowing an easier identification of anatomic structures and an easier surgical performance in difficult cases. The most common applications in pediatric surgery include varicocele repair, difficult cholecystectomy, partial nephrectomy, lymphoma and tumors excision but further indications will be soon discovered. ICG-enhanced fluorescence was technically easy to apply and safe for the patient reporting no adverse reactions to the product. The main limitation is represented by the specific equipment needed to apply ICG-guided NIRF in laparoscopic procedures, that is not available in all centers whereas the ICG system Firefly® is already integrated into the robotic platform.